PENGEMBANGAN MEDIA TICASA UNTUK MENINGKATKAN PEMAHAMAN BILANGAN BESAR SISWA KELAS III SDN BUKIT DURI 01 JAKARTA - Wulan Kusuma Ningrum; Ramadhani, Sulistyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Understanding the concept of large numbers remains a challenge for third-grade elementary school students, primarily due to the lack of concrete media that support abstract learning. This study aims to develop and test the feasibility and effectiveness of TICASA (Magnetic Large Numbers) learning media in improving the understanding of large numbers. The study was conducted at SDN Bukit Duri 01 Jakarta using the ADDIE Research and Development (R&D) model. The subjects were third-grade students. Data were collected through interviews, questionnaires, documentation, and pretests and posttests. Validation was carried out by material experts and design experts, with feasibility results of 94% and 93%, respectively. The media was then tested on small groups (5 students), medium groups (10 students), and large groups (24 students). The results showed a significant increase in student understanding, with an average N-Gain reaching 0.81 (high category) and feasibility levels of 73.23%, 81.41%, and 81.74%, respectively. Students and teachers responded positively to the media, both in terms of visualization and ease of use. TICASA has been proven to help bridge abstract concepts into concrete ones, increasing student motivation and learning participation. In conclusion, TICASA media is feasible and effective for use in mathematics instruction on large numbers in third grade elementary school. Widespread use of this media is recommended with the support of further training and development.